Numerical Simulation of the Construction Process of Long Spiral CFG Piles - Taotao Wang; Siyi Du (Advances in Civil Engineering)
A numerical model for the construction process of long spiral CFG piles is established based on the coupled Eulerian–Lagrangian method. The construction process is divided into drilling process and concrete pouring process for modeling. The influence of long spiral CFG piles construction on saturated sand foundation is studied, and dynamic responses, changes of pore water pressure, and void ratio of saturated sand foundation are obtained. The rationality and accuracy of the simulation results are proved by comparing with the field test data and calculation results of the theory of cylindrical cavity expansion. The presented numerical results prove that the vibration load generated during the construction acts on saturated soil in the form of irregular reciprocating shear forces, which leads to a large excess pore water pressure in the soil and an increase in soil void ratio. Both the excess pore water pressure field generated during the construction and the soil pore ratio after the construction show a parabolic distribution in the vertical direction. The research results can provide reference and theoretical basis for future research and engineering practice.